Development of new magnetic adsorbent of walnut shell ash/starch/Fe3O4 for effective copper ions removal: Treatment of groundwater samples. (June 2022) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Mohammadi, Reza; Peighambardoust, Seyed Hadi; Ramavandi, Bahman
Abstract: The goal of this investigation was to develop a new magnetic nanocomposite of walnut shell ash (WSA)/starch/Fe3 O4 to remove Cu (II) present in groundwater samples. The desired nanocomposites were successfully synthesized by the chemical deposition method. The specific active surface area for pristine WSA and WSA/starch/Fe3 O4 magnetic nanocomposites was determined to be 8.1 and 52.6 m 2 /g, respectively. A central composite design for the response surface method was utilized to study the influence of pH, adsorbent quantity, initial content of Cu (II), temperature, and contact time. This method showed the success of the model to design process variables and to estimate the appropriate response. The P - and F -value determined for the quadratic polynomial model showed the significance and accuracy of the proposed model in examining experimental and predicted data with R 2 and Adj.R 2 of 0.994 and 0.991, respectively. The Cu adsorption onto WSA and WSA/starch/Fe3 O4 obeyed the Freundlich and Langmuir models, respectively. The highest Cu (II) sorption capacity of 29.0 and 45.4 mg/g was attained for WSA and WSA/starch/Fe3 O4, respectively. The free energy of Gibbs had a negative value at 25–45 °C indicating that the adsorption process is spontaneous. Also, negative ΔH values for copper adsorption showed that the processes are exothermic. The kinetic adsorption data for WSA and WSA/starch/Fe3 O4 followed the pseudo-second order (PSO) model. The ability of the composite adsorbent to remove copper from three groundwater samples showed that it could be reused at least 3 times with appropriate efficiency, depending on the water quality. Graphical abstract: Cu ion removal using walnut ash/starch/Fe3 O4. Image 1 Highlights: The walnut shell ash (WSA) was composited with starch and Fe3 O4 . The BET value for WSA and WSA/starch/Fe3 O4 was 8.1 and 52.6 m 2 /g, respectively. The Cu removal by WSA/starch/Fe3 O4 followed pseudo-second order and Langmuir model. The Cu sorption capacity of WSA/starch/Fe3 O4 was obtained 45.4 mg/g. Groundwater samples were efficiently treated by WSA/starch/Fe3 O4 .